Determination of cable tensile forces using paraseismic effects - Papán Daniel; Papánová Zuzana (MATEC Web of Conferences, 2020)
By construction or by reconstruction of civil structures can be paraseismic load generated. This effect may causes cracks in buildings standing near the source of the vibrations. Numerical simulation is one of the possibilities how can be this problem analyzed. The vibrations velocities of source transmitted to the surrounding buildings can be used as excitation to the numerical simulations. In the paper is presented the case study of the assessment of the tension forces in load bearing cables in real civil structure. This estimation is based on theoretical and experimental dynamic equations comparison.